PEMBANGUNAN APLIKASI FORUM SEBAGAI SALAH SATU TOOLS KNOWLEDGE MANAGEMENT SYSTEM DENGAN PENDEKATAN INSTANT MESSAGING AND INTRANET FORUMS PADA PT ABI MAJU KONSULTAN DI PONTIANAK - Hasanudin Hasanudin (Jurnal Khatulistiwa Informatika, 2014)
Knowledge is a valuable asset for everyone no exception for the company. By Herbert (2007) Knowledge of a person can grow because of the experience, successes and failures and the learning process that meet all the time. Knowledge it self is divided into two parts that is "tacit knowledge" and "explicit knowledge". Storage of knowledge possessed by employees in companies is an effective way. According to Purnomo (2011, p.3) Knowledge Management System (KMS) is a system that is able to classify existing knowledge, seek knowledge, conduct and maintain knowledge of storage and use. At PT Abi Maju Konsultan, the workers knowledge still preserved, so in the event one of the employees who left the company so when recruiting new employees, the company will conduct initial training of the work that will be occupied employee. Making an application with the forum knowledge management system approach Intranet Instant Messaging And Forums is expected to address the problem so that the knowledges possessed by employees can be stored and can be used at any time when needed.Keyword: Knowledge management system, forum, knowledge